Pelatihan Food Hygiene dan Personal Hygiene Bagi Karyawan Hotel di Kota Semarang - Prima Setia Judha Pranatha; Izza Ulumuddin Ahmad Asshofi; Emik Rahayu; Dedi Joko Purnomo; Veronica Halim; Indah Indah (Jurnal Pengabdian Masyarakat Waradin, 2025)
Tourism is an activity in which a person travels for recreation or vacation. Tourism is also associated with the need for stopovers and overnight accommodations. Not only for overnight needs, meeting rooms, sports halls and restaurants are now mandatory facilities in a hotel and are needed according to the type of hotel. The hotel restaurant provides catering services, in this case it must also meet hygiene requirements. Food hygiene is the prevention of disease by maintaining high standards of hygiene and the quality of the food itself. Personal hygiene is the human way of self-care to maintain good health. Food and personal hygiene of food workers in the food processing process is very important because applying good hygiene can minimize the possibility of food contamination. The application of food health and personal hygiene can be influenced by one's knowledge about it in the workplace. Lack of food health knowledge and personal hygiene can be improved by providing information and education through counseling or training. The training held was a collaboration between IHGM DPD Central Java partners and the team proposing Dian Nuswantoro University through a community service or community partnership program whose implementation was in the form of training on Food Hygiene and Personal Hygiene for hotel employees in the city of Semarang